Open gyms and physical activity in a university setting: A mixed-methods study from Varanasi, India - Lalita Vatta; Upasana Pandey; Anchal Pandey; Bindyashwori Yelam; Neha Rathi (Journal of Health, Population and Nutrition)
Abstract Background The prevalence of physical inactivity in India is estimated to be 34%; the highest prevalence in South Asian countries. Physical inactivity has increased the risk of non-communicable diseases among urban Indians. Built environment interventions that aim to enhance physical activity have gained popularity in recent years. The construction of outdoor gymnasiums (hereafter referred to as OGs) in green spaces is one such intervention. The installation of OGs on university campuses is a novel concept. The present study was designed to explore the usage of OGs and the perceptions of the users about OGs in a public university setting. Methods A sequential mixed-methods study design was used to inform this two-fold study. In the first phase (Quantitative), four OGs (i.e. OG-A, OG-B, OG-C, OG-D) were observed between 6.00 am and 8.00 pm for one week per month from December 2022 to March 2023 which corresponds to winter and spring time in Varanasi, India. In the second phase (Qualitative), face-to-face, semi-structured in-depth interviews (N = 66) with a purposive sample of (OG) users were conducted in Hindi. Descriptive statistics and thematic analysis were used to analyze quantitative and qualitative data respectively. Results Observational data revealed that the OGs were more frequently used during spring as compared to winter. OG-C emerged as the most popular gym across the four-month period as it hosted the highest number of users (N = 3384) followed by OG-D (N = 2380), OG-B (N = 2004), and OG-A (N = 792). Another major observation was that OGs were more likely to be used by males than females. OGs were more crowded over weekends than weekdays. The thematic analysis of qualitative interview data revealed three main themes and associated sub-themes: (i) Perceived benefits associated with the use of OGs (physical and mental health benefits, proximity to nature, opportunity to socialize, safe environment, economical, ease of access for everyone); (ii) Perceived challenges associated with the use of OGs (lack of time, overcrowding, damaged equipment, laziness); (iii) Feedback for improvement of OGs (regular maintenance of gym equipment, installation of more equipment, installation of drinking water stations and restrooms). Conclusions The emerging findings recognize OGs as viable built environment interventions that encourage people to embrace physical activity. The OGs not only contribute to the revitalization of open green spaces in university campuses where they are installed but also play a significant role towards the fulfilment of social responsibility of educational institutions.